2015
DOI: 10.1016/j.jneumeth.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the time for accurate EEG decoding of single value-based decisions

Abstract: h i g h l i g h t s• We outline a novel method for assessing time-unlocked topographic EEG activity.• We apply this method for accurately predicting accept vs. reject decisions.• The time when decisions have been made is modulated by task difficulty.• It occurs well before subjects' button press (∼340 ms).• This time is compatible with a diffusion process, evaluated at behavioral level. a r t i c l e i n f o b s t r a c tBackground: Recent neuroimaging studies suggest that value-based decision-making may rely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…We (Goto et al, 2017) found that viewing a group of highly preferred (HP) consumer goods led to more positive N200, LPP and PSW amplitudes compared to viewing less preferred (LP) goods. These results are consistent with results showing that preferences for pictorial figures as well as food items could modulate electrophysiological activity as early as 150 ms after stimulus onset, and up to 800 ms (Harris et al, 2011; Tzovara et al, 2015). Further, Pozharliev et al (2015) did report effects of preference for luxury goods on the LPP, and Ma et al (2018) reported larger LPP amplitudes for prices that could lead to buying intentions.…”
Section: Introductionsupporting
confidence: 92%
“…We (Goto et al, 2017) found that viewing a group of highly preferred (HP) consumer goods led to more positive N200, LPP and PSW amplitudes compared to viewing less preferred (LP) goods. These results are consistent with results showing that preferences for pictorial figures as well as food items could modulate electrophysiological activity as early as 150 ms after stimulus onset, and up to 800 ms (Harris et al, 2011; Tzovara et al, 2015). Further, Pozharliev et al (2015) did report effects of preference for luxury goods on the LPP, and Ma et al (2018) reported larger LPP amplitudes for prices that could lead to buying intentions.…”
Section: Introductionsupporting
confidence: 92%
“…One cluster of activity occurred frontocentrally directly after the modelfree prediction error. Studies by Tzovara, et al (2015), Fischer and Ullsperger (2013) and Hunt, et al (2012) (using MEG), employing tasks in which variably valuable choices were presented at the start of a trial have also successfully demonstrated neural signatures of Q values. Also, in an experiment employing the same two step task as that used here, Eppinger, et al (2017) showed state action Q values at state 2 at a comparable latency (400 ms) to ourselves, though more parietally.…”
Section: The Demonstration Of Model-based Rpes Does Not Resolve the Qmentioning
confidence: 96%
“…Subjective or cognitive performance measures have been employed in the analysis of single-trial evoked potential data to separate noise variance from the meaningful information about the perceptual decisions occurring with each stimulus. Mapping behavioural data onto brain electrical activity requires a statistical model, such as a multiple linear regression model (Ratcliff et al 2009 ; Rousselet et al 2011 ), support vector machines (Schulz et al 2012 ), multivariate decoding based on accumulation of topographic activity (Tzovara et al 2015 ), or a linear fixed effects model (Michail et al 2016 ). While single-trial analysis of evoked potentials was previously performed using a variety of methods, the multiple regression analysis utilised here fitted the objective to associate multiple aspects of subjective pain experience with the P2 component whilst accounting for possible inter-correlations between predictors.…”
Section: Methodsmentioning
confidence: 99%